2019
DOI: 10.1111/jhn.12682
|View full text |Cite
|
Sign up to set email alerts
|

Associations of dietetic management with maternal and neonatal health outcomes in women diagnosed with gestational diabetes: a retrospective cohort study

Abstract: How to cite this article Absalom G., Zinga J., Margerison C., van der Pligt P. (2019) Associations of dietetic management with maternal and neonatal health outcomes in women diagnosed with gestational diabetes: a retrospective cohort study. J Hum Nutr Diet. 32, 728-736 https://doi. AbstractBackground: In 2010, the recommended diagnostic thresholds for gestational diabetes mellitus (GDM) were amended, which has increased GDM diagnoses, as well as pressure on the services involved in GDM management, specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Identifying these barriers is the first step in developing tailored implementation strategies 29‐32 . Lack of dietetic staffing has been reported as one of the greatest barriers to GDM guideline implementation in several studies given the frequency of visits recommended (one initial visit and two or more reviews) 33–35 . Given the rising rates of GDM globally and concurrent increases in clinical workload, this is not surprising 11,12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying these barriers is the first step in developing tailored implementation strategies 29‐32 . Lack of dietetic staffing has been reported as one of the greatest barriers to GDM guideline implementation in several studies given the frequency of visits recommended (one initial visit and two or more reviews) 33–35 . Given the rising rates of GDM globally and concurrent increases in clinical workload, this is not surprising 11,12 .…”
Section: Discussionmentioning
confidence: 99%
“… 29 , 30 , 31 , 32 Lack of dietetic staffing has been reported as one of the greatest barriers to GDM guideline implementation in several studies given the frequency of visits recommended (one initial visit and two or more reviews). 33 , 34 , 35 Given the rising rates of GDM globally and concurrent increases in clinical workload, this is not surprising. 11 , 12 However, despite these challenges, several Australian studies have developed models of care aimed at increasing provision of evidence‐based MNT for GDM.…”
Section: Discussionmentioning
confidence: 99%
“…In a group of Canadian women, 17 with GDM and 27 with normal glucose tolerance, Morisset et al (2014) demonstrated that a multidisciplinary medical and nutrition intervention, including counselling from a registered dietitian, was effective in the achieving prescribed macronutrient distributions and controlling gestational weight gain in women with GDM. Other studies have demonstrated further benefits of dietetic input in women with GDM, including reduced insulin use and improvements in glycated haemoglobin [69] and reduced likelihood of infant admission to neonatal intensive care or special care units [70].…”
Section: Discussionmentioning
confidence: 99%
“…The structure of these clinics varies across New Zealand regions but typically include a diabetes physician, obstetrician, diabetes midwife or diabetes specialist nurse and a dietitian. Although studies have found dietetic input to be associated with positive outcomes for women with GDM [ 23 25 ] surveys of dietetic practice have identified some inconsistencies in the services provided and recommendations made to women with GDM with some women with GDM not seeing a dietitian at all [ 26 29 ]. Furthermore, women are exposed to nutrition messages from several sources which may be inconsistent or incomplete [ 30 33 ] leading to confusion about what to do and a lack of confidence in recommendations [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%